Connoisseurship, consumption, company, and James Brydges, first Duke of Chandos, 1705–13 - Graham, A (Penn Press, 2018)
Between 1705 and 1713, James Brydges (later the first Duke of Chandos) was both a public official and a private collector and connoisseur. These roles have been seen as separate and even incompatible, as the personal connections required for collecting artworks from Europe cut across the impersonal, bureaucratic standards expected from officials. Drawing on Brydges's extensive correspondence, Aaron Graham argues that the process of collecting and connoisseurship in fact made him a far more effective public official. Recent work has shown that public service in this period often required officials to cultivate relationships with the merchants and financiers who acted as contractors for state business. A shared process of collecting, appreciating, and consuming goods, including such mundane items as wine, helped to strengthen connections.